IKLAN INDOMIE (DARI SABANG SAMPAI MARAUKE) SEBAGAI REPRESENTASI KEBUDAYAAN INDONESIA - DANIEL DE RETES (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2016)
Indomie Advertisement (Dari Sabang Sampai Marauke) as Indonesian Culture Representation. Advertisement is a mass culture product which shaping behaviour and life pattern of human. Music become advertising power to deliver information about the product offerd. Indomie advertisiment which the theme was Dari Sabang Sampai Merauke had culture dimension of Indonesia through the image of ‘the singing society’ which can be seen as visually and musically. This discussion was an effort of studying musical elements from the advertisement through critical analysis for showing how Indomie advertisement which represent Indonesian culture can dwells within society.